New Materials for SLS: The Use of Antistatic and Flow Agents. (2nd June 2016) - Lexow, Matthias Michael; Drummer, Dietmar
Abstract : Selective laser sintering (SLS) is a process based on the principle of a locally confined energy input by a laser into a powder bed, producing highly complex parts without the use of moulds or any other tools. In order to ensure good results for the processing behaviour of a new material, the powder must perform well during the phase of feeding the material into the process chamber which majorly influences the quality of the spread of the powder into the part bed and thus the mechanical performance of the final parts. In the present study, the principle of modification of fine powders with flow agents is applied aiming to enable the use of powders for SLS which are otherwise unsuitable due to poor flowability. In addition, the influence of antistatic agent on the powder flow and processing behaviour is discussed. The additives are found to strongly improve the flow behaviour at already very small contents and thus allow for processing of the composite material. The development of determining factors shares insight into the mechanisms of dry particle coating and its implementation into a growing market of material development.